2011
DOI: 10.1021/ja203822q
|View full text |Cite|
|
Sign up to set email alerts
|

Segregated Donor–Acceptor Columns in Liquid Crystals That Exhibit Highly Efficient Ambipolar Charge Transport

Abstract: Liquid crystalline donor (i.e., phthalocyanine) was covalently linked to acceptor (i.e, fullerene) to achieve efficient charge-transport properties in a liquid crystalline phase. The columnar structure exhibited highly efficient ambipolar charge-transport character, demonstrating the potential utility of the strategy in organic electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 41 publications
3
115
0
2
Order By: Relevance
“…The helical structure very resembles spiranthes flowers, so that we named this unique structure as "spiranthes-like supramolecular structure" [31,32]. On the other hand, in 2010-11 Imahori and Shimizu joint research group also reported the helical structure of C 60 moieties in a Pc-C 60 dyad [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The helical structure very resembles spiranthes flowers, so that we named this unique structure as "spiranthes-like supramolecular structure" [31,32]. On the other hand, in 2010-11 Imahori and Shimizu joint research group also reported the helical structure of C 60 moieties in a Pc-C 60 dyad [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, the first liquid crystals based on phthalocyanine fullerene (Pc-C 60 ) dyad ( Fig. 1[A]) were reported by our group in 2006 [10][11][12][13][14][15][16][17][18][19][20][21][22] and then Geerts group in 2009 [14]. Among our liquid crystalline Pc-C 60 dyads, we found at the first time in 2006 that some of the Pc-C 60 dyads exhibit perfect homeotropic alignment between two glass plates ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can greatly reduce their costs to manufacture the solar cells. Liquid crystalline D-A systems are braodly classified into three groups: smectic liquid crystals [1][2][3][4], liquid crystalline copolymers [5][6][7][8][9][10][11][12] and discotic columnar liquid crystals [13][14][15][16][17][18][19][20][21][22][23][24][25]. In 2004 Kim et al reported that an organic photovoltaic cell was fabricated by using liquid crystalline N,N'-diheptyl-3,4,9,10-perylenetetracarboxylicdiimide (PTCDI-C7) as the electron acceptor and zinc phthalocyanine (ZnPc) as the electron donor [1].…”
Section: Introductionmentioning
confidence: 99%
“…Compound 11 with a rigid spacer does not show liquid crystalline properties, whereas compound 12 with a flexible spacer self-organizes in a rectangular columnar mesophase. Hayashi et al 67 covalently linked a Pc donor with a fullerene acceptor. The columnar structure formed by compound 13 exhibits highly efficient charge transport properties.…”
Section: Dlc-np Hybrid Systems S Kumarmentioning
confidence: 99%